Recent Advances in Immune Cell Therapy for Glioblastoma - Kang, Xianhui; Zheng, Yiyang; Hong, Wandong; Chen, Xixi; Li, Huiting; Huang, Baojun; Huang, Zhenyang; Tang, Hongli; Geng, Wujun (Frontiers in Immunology, 2020)
Glioblastoma (GBM) is the most malignant form of astrocytoma, with short survival and a high recurrence rate, and remains a global problem. Currently, surgery, chemotherapy, radiotherapy and other comprehensive treatments are the main treatment modalities, but patients still have a poor prognosis mainly due to the infiltrative growth of GBM and the protective effect of the blood–brain barrier (BBB) on tumor cells. Therefore, immunotherapy is expected to be a good option for GBM. In the immune system, different cells play varying roles in the treatment of GBM, so understanding the roles played by various immune cells in treating GBM and considering how to combine these effects to maximize the efficacy of these cells is important for the selection of comprehensive and optimal treatment plans and improving GBM prognosis. Therefore, this study reviews the latest research progress on the role of various types of immune cells in the treatment of GBM.